CREATING AN ANIMATED CHARACTER FOR A COMPUTERIZED DEAF TRANSLATION SYSTEM - Nurgazina, D.M.; Kudubayeva, S.A.; Bekbauova, A.U. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article explores the diversity of sign languages using 3D avatars in the context of deaf translation. The research aims to develop algorithms and a 3D avatar based on the visual characteristics of sign language. Special attention is given to the formalization of algorithms and the development of code for 3D avatars, serving as visual demonstrators in sign language translation. Differences between post-Soviet languages using Russian sign language and Kazakhstan, which employs its sign language, are analyzed. The results of the research on the 3D avatar for Turkish sign language are presented, including code development and efficiency evaluation, considering the possibility of algorithm formalization. The research methodology involves analyzing and comparing Kazakh sign language with Turkish attempts or the potential adoption of the Latin script in Kazakhstan. Using a Turkish 3D demonstrator, an animated character model has been created for a computerized sign language translation system into Kazakh Sign Language. The creation of the model utilized the cross-platform graphical package Unity3D. The concluding part emphasizes the significance of such innovations in sign language and their potential application in improving communication for individuals with hearing impairments.